Study on the Relationship Between Peritoneal Dialysis Ultrafiltration Failure and Aquaporin 1, Aquaporin 3, and Vascular Endothelial Growth Factor A Expression (Iranian Journal of Kidney Diseases, 2022)
Introduction. The aim of this study was to investigate the expression of aquaporin 1 (AQP-1), AQP-3 and vascular endothelial growth factor A (VEGF-A) in peritoneal tissues of patients without kidney disease, chronic kidney disease at stages 5 (CKD 5) and patients on prolonged peritoneal dialysis with ultrafiltration failure (PDUFF), and elucidate the possible mechanism of peritoneal dialysis ultrafiltration failure. Methods. Peritoneal specimens were collected from the following patient groups at Xianju People’s hospital: CKD 5, PD-UFF and normal control groups. Routine staining and immunohistochemical analyses were performed on samples obtained from the three groups. Results. The expression of AQP-1 and AQP-3 on peritoneal mesothelial cells, peritoneal vessels and in the interstitium was significantly lower in the PD-UFF group than the CKD 5 and control groups (P < .01), while no statistically significant difference was found between the CKD 5 and control groups (P > .05). In contrast, VEGF-A expression was significantly higher in peritoneal mesothelial cells, peritoneal vessels and the interstitium in the PD-UFF group than the CKD 5 and control groups (P < .01). No statistically significant difference was found between the CKD 5 and control groups (P > .05). Conclusion. AQP-1 and AQP-3 expression levels decrease in peritoneal mesothelial cells and the vascular interstitium of patients with a prolonged peritoneal dialysis course, while VEGF-A expression gradually increases. The formation of peritoneal neovascularization and the decrease in AQP expression may be primarily associated with peritoneal dialysis ultrafiltration failure.  DOI: 10.52547/ijkd.6928